Very Low Hepatitis C Viral Loads in Treatment-naive Persons: Do They Compromise Hepatitis C Virus Antigen Testing?. (3rd April 2019) - Bertisch, Barbara; Brezzi, Matteo; Negro, Francesco; Müllhaupt, Beat; Ottiger, Cornelia; Künzler-Heule, Patrizia; Schmid, Patrick; Giudici, Fabio; Clerc, Olivier; Moriggia, Alberto; Roelens, Maroussia; Marinucci, Francesco; et al.
Abstract: Background: Hepatitis C virus (HCV) antigen testing is less expensive than quantitative reverse-transcription polymerase chain reaction but has lower sensitivity for very low viral load (VLVL; HCV RNA ≤3000 IU/mL). Currently the benefits of antigen testing for screening are discussed, but data on prevalence and outcomes of persons with VLVL are scarce. Methods: We assessed prevalence and predictors of VLVL by logistic regression in treatment-naive participants in the Swiss Hepatitis C Cohort Study. We analyzed if the last viral load after VLVL was low, compared cirrhosis and mortality in persons with and without VLVL, and evaluated the number of samples with VLVL that were reactive by antigen testing. Results: We included 2533 treatment-naive persons with available quantitative HCV RNA testing results. Overall, 133 persons (5.3%) had a VLVL. Age 18–40 years, female sex, and human immunodeficiency virus coinfection were associated with VLVL. Of 72 persons with a viral load available after VLVL, 14% had a VLVL and 17% had spontaneous viral clearance. The prevalence and incidence of cirrhosis and mortality were comparable in persons with and without VLVL; all 24 persons with VLVL and cirrhosis had excessive alcohol consumption or immunosuppression. Overall, 33% of samples with VLVL were reactive by antigen testing. Conclusions: The frequency of VLVL was low. Among the persons who would probably be missed by antigen screening, some had a favorable disease course, but some had immunosuppression and liver cirrhosis. The benefit of HCV antigen testing for screening may be limited by the risk of missing patients with severe liver disease. Abstract : Among 2533 chronically hepatitis C–infected, treatment-naive persons in the Swiss Hepatitis C Cohort Study, 133 persons (5.3%) ever had a viral load ≤3000 IU/mL. Part of these showed favorable disease courses, but 24 persons, all immunosuppressed, had cirrhosis.